Co-creating and delivering personalized, nature-based VR experiences: Proof-of-concept study with four U.S. adults living with severe COPD - O. McAnirlin; M.H.E.M. Browning; T. Fasolino; K. Okamoto; I. Sharaievska; J. Thrift; J.K. Pope (Wellbeing, Space and Society)
Severe chronic obstructive pulmonary disease (COPD) makes visiting outdoor spaces difficult. This proof-of-concept study tapped into personally meaningful outdoor memories to co-create and deliver personalized nature-based VR experiences with four adults living in upstate South Carolina, U.S. Our study objective was to evaluate participant responses to the co-creation process and VR experience. We identified familiar landscapes with each participant, captured 360-degree videos of these locations, and worked with them to select the videos, audio, and sequences to use. Each participant co-created and then experienced their own unique 5–7 min 360-degree video in a VR headset. Participant responses were measured with questionnaires on psychological well-being, perceived restoration, cybersickness, and presence, along with physiological data on heart rate, heart rate variability, respiratory rate, and blood oxygen levels. Our findings generally supported that the co-creation process and personalized, nature-based VR experience was safe for our participants and could support their psychological well-being. More broadly, this study supports additional research with these activities to promote well-being among people living with chronic disease.